Experimental and numerical study of auxetic sandwich panels on 160 grams of PE4 blast loading. (November 2021) - Arifurrahman, Faizal; Critchley, Richard; Horsfall, Ian
Mines, specifically as Anti-Tank (AT) mines are a significant threat for defence vehicles. While approaches such as v-shaped hulls are currently used to deflect the blast products from such threats, such a solution is not always usable when hull standoff is limited. As such the development of a low profile, energy absorbing solution is desirable. One approach that has potential to achieve these requirements are sandwich panels. While sandwich panel cores can be constructed from various materials, one material of particular interest are auxetics. Auxetic are materials that exhibit a negative Poisson's ratio. This material has potential to be an efficient an impact energy absorber by increasing stiffness at local deformation by gathering mass at the impact location. This study investigates the effectiveness of novel auxetic core infills alongside three other panel types (monolithic, air gap, polymer foam sandwich) against buried charges. 160 grams of PE4 were buried in 100 mm depth and 500 mm stand off the target. Laser and High Speed Video (HSV) system were used to capture the deflection-time profile and load cell sensors were used to record the loading profile received by the panels. Experimental works were compared with numerical model. Explicit model were generated in LSDYNA software as 'initial impulse mine' keyword. The result found that the auxetic and foam core panels were effective in reducing peak structural loading and impulse by up to 33% and 34% respectively. Air-filled panels were the most effective to reduce the deflection of the rear of the plate, however variation between capture methods (HSV and Laser system) were reported, while numerical modelling provided comparable plate deflections responses. When normalised against panel weight, the air filled panels were experimentally the most efficient per unit mass system with the auxetics being the least effective.